Think about the formulation of a national supporter of transparency and anti-corruption among the various sectors of the State in Iraq (مجلة المنصور, 2022)
It became clear that the processes of building integrity and transparency and anti-corruption should top the priorities of reform efforts necessary to activate the economic development and sustainability, and dissemination of the rinciple of transparency to all activities, programs and investment projects is crucial in Iraq to make it free of corruption types.The problem with research in the continued prevalence of abuse of public power for personal use which could lead to corruption in the civil society and thus undermine the civil state, which aspires to Iraqi society, and the importance of research in raising the awareness of civil society in Iraq of the importance of transparency as a tool for the prevention of corruption, and toshed light on the experiences of countries able to build a national ideology in the fight against corruption and worked on its implementation through a variety of tools.The research aims to illustrate the importance of the activities and programs that will make Iraq free of the kinds of corruption, and the role of BSA in support of transparency in cooperation with all actors of society, institutions and individuals. The research found some of the findings and recommendations for activating the activities and programs that will make Iraqfree of corruption.